Case Report: Urgent ultrasound-guided dual-lumen PICC placement after platelet transfusion in severe aplastic anemia with extreme thrombocytopenia - Yeyan He; Shasha Li; Yimei Feng; Xiaoli Chen; Xi Zhang (Frontiers in Medicine, 2026)
Background Patients with severe aplastic anemia (SAA) proceeding to allogeneic hematopoietic cell transplantation (HCT) require reliable central venous access, yet the procedural evidence base was generated at platelet counts of roughly 10–50 × 10 9 /L and does not extend to the extreme thrombocytopenia of marrow failure. Case description A 56-year-old woman with SAA, neutropenia, fungal maxillary sinusitis, scattered ecchymoses, and no active spontaneous bleeding required urgent multi-lumen access before conditioning. Her admission platelet count was 1 × 10 9 /L, and after one 200-mL apheresis platelet transfusion the count measured approximately 14 h later was 2 × 10 9 /L, a poor sustained increment. Because that sample fell outside any standardized post-transfusion interval, a corrected count increment could not be calculated and refractoriness could not be established; HLA and HPA antibody testing was not available within the procedural window. Intervention and outcomes After multidisciplinary review, a second 200-mL apheresis platelet transfusion was given and a 5-Fr dual-lumen power-injectable PICC was inserted immediately afterward through the right basilic vein under ultrasound guidance. Insertion followed the transfusion without an interval, so the last recorded count of 2 × 10 9 /L precedes the second unit and the value at venipuncture was not remeasured. The catheter-to-vein ratio, measured from the stored procedural images, was approximately 32%. Access was achieved on the first puncture and the tip confirmed in the lower third of the superior vena cava. World Health Organization grade 1 puncture-site oozing stopped after 10 min of compression. No bleeding of grade 2 or higher, transfusion reaction, occlusion, migration, catheter-related bloodstream infection, or clinically evident catheter-related thrombosis was documented over 63 catheter-days or at 3-month follow-up. Routine thrombosis-screening ultrasound was not performed. Conclusion This report documents how a coordinated risk-control pathway combining necessity assessment, platelet support, a compressible access site, first-pass ultrasound-guided insertion, and interval-specific surveillance was applied when transplantation could not be deferred, and it specifies the measurements that future prospective series should capture. A single case cannot establish the safety of PICC placement at extremely low platelet counts or define a platelet threshold, particularly because the count at the time of insertion was not remeasured.